Memahami Contextual Performance Sebagai Sikap Kerja Positif - Aprilyanna (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2022)
In the development of industries and organizations in Indonesia, there is one important variable, namely contextual performance. Contextual performance is one of the important variables because it can produce a positive work environment for industry and organizations. Although contextual performance is not considered as part of the main task (non-formal) by the performance system, contextual performance contributes more to maintaining the social system in the organizational environment as a positive work attitude. The method used in this journal is literature review research, which is collecting research journals and books based on the issues raised to provide a new, detailed description of the contextual performance issues. the result is that this work attitude does not show the results of the impact immediately, but will be seen in the long term. This scientific article focuses on providing an understanding of contextual performance by using the literature study method